(3TQM bGfhf GdYbhHGJ (B:s ((3GdbSe GdYGe(B) : ((3GdfXQjI GdYGeI ddYbhHI(B) /s - (3GdeQGZj, CMeO YHO GddGgs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3jJfGhd gPG GdcJGH TQM bGfhf GdYbhHGJ hPdc aj SHYI aUhd OGQJ Mhd (B((3GdCMcGe GdYGeI ddYbhHI hCfhGY GdYbhHGJ hJbSjeGJgG hGdYbhHGJ GdCUdjI hGdYbhHGJ GdJHYjI hGdJcejdjI hGdJWHjb GdbVGFj ddYbhHI hJYOO GdLQGFe hCKQg aj GdYbhHI hWQb GfbVGA GdYbhHI(B) (3MjK GdYbhHI TQ jbGHd GdCKe GdPj GQJcHg GdLGfj jMce HgG Ydi ef JKHJ eSFhdjJg GdLfGFjI Yf GdLQjeI GdJj GQJcHJ hdgG CZQGV eJfhYI hGdYbhHGJ aj GdbGfhf GdLfGFj dG JMhd Ohf QOY GdeLQe abW Yf GQJcGH GdLQjeI(B.s
(3GdeMJhjGJ (B: (3GdaUd GdChd (B: (3GdCMcGe GdYGeI ddYbhHI(B-(3GdeHMK GdChd (B: (3JYQja GdYbhHg(B-(3GdeHMK GdKGfj (B: (3LhgQ GdYbhHI GdLfGFjI(B... -(3GdaUd GdKGfj (B: (3CfhGY GdYbhHGJ hJbSjeGJgG(B-(3GdeHMK GdChd (B: (3GdYbhHGJ ef MjK LSGeJgG(B-(3GdeHMK GdKGfj (B: (3GdYbhHGJ ef MjK eMdgG(B... -(3GdaUd GdKGdK (B: (3GdYbhHGJ GdCUdjI(B-(3GdeHMK GdChd (B: (3GdYbhHGJ GdESJFUGdjI(B-(3GdeHMK GdKGfj (B: (3GdYbhHGJ GdSdGdHI ddMQjI(B... -(3GdaUd GdQGHY (B: (3GdYbhHGJ GdJHYjI hGdJcejdjI(B-(3GdeHMK GdChd (B: (3GdMQeGf ef GdMbhb hGdeRGjG(B-(3GdeHMK GdKGfj (B: (3GdYRd ef GdhXGFa GdYGeI(B... -(3GdaUd GdNGeS (B: (3GdJWHjb GdbVGFj ddYbhHI(B-(3GdaUd GdSGOS (B: (3JYOO GdLQGFe hCKQg aj GdYbhHI(B-(3GdaUd GdSGHY (B: (3WQb EfbVGA GdYbhHI(B.s
(3HHdjhLQGajI (B: (3UaMI (B295-315.s
Keywords: (3bGfhf GdYbhHGJs -- (3eUQs; (3GdCMcGe GdLfGFjIs -- (3eUQs; (3GdLRGAGJ GdJCOjHjI s; (3GdYbhHGJ GdeGSI HGdMQjIs; (3GdYbhHGJ GdSGdHI ddMQjIs; (3GfbVGA GdYbhHI s; (3JbGOe GdYbhHIs; (3GdbGfhf GdLfGFjs